Kesulitan Belajar Mahasiswa dalam Praktikum Biokimia Online: Pengalaman Selama Covid-19 - Rahmah Qonita; Muhammad A'tourrohman; Ulwiyah; Erna Wijayanti (BIOEDUSCIENCE, 2021)
Background: Covid-19 pandemic changed all aspects of human life, including education. Biochemistry practicum activities that should be carried out in the laboratory must be done online. This study analyzes students' learning difficulties in carrying out biochemical online practicum in the Covid-19 pandemic era. Methods: This research uses the descriptive qualitative method. The Sample consisted of 63 respondents from students majoring in biology education at UIN Walisongo. The instrument used was a questionnaire with The Gutman scale. Data analyzed using percentage difficulty analysis. Results: the implementation of online biochemistry practicum experienced less difficulties. The percentage of barriers in the difficult category is, material mastery barriers 30,5%, practical implementation barriers 28,8%, internal barriers 25,8%, and external barriers 36,6%. Conclusions: Selection of appropriate learning methods and media is needed to make it easier for students to understand online practicum material.